Analisis Mirror Server menggunakan Load Balancing pada Jaringan Area Lokal - Alfian Nurdiansyah; Nugroho Suharto; Hudiono Hudiono (Politeknik Negeri Malang, 2020)
A Server is a system that provides certain services on a computer network. The Server has its own operating system called the network operating system. The Server also controls all access to existing networks. In order to help server tasks, a server mirroring system is set up where the server is duplicating a data sets or an exact clone of a server providing various information. Mirror server or also called Server synchronization is a duplicate of a server. To add performance from the server, a load balancer is required. Load balancing is a technique for distributing two internet connection paths equally. With the application of load balancing the traffic will run more optimally, maximizing throughput, and avoiding overload on the connection path. Iptables is used for IP filtering so the clients could access the server according to the closest server zone, so that the load balance combined with iptables can reduce the server's load. A common problem is when many clients access a server and the server will overload and cause the server performance to be slow because of the heavy traffic. The access Client also get the effect of this, which is slow response time. From the result of research on the combination of load balance and iptables, it was found that the load balance with the round robin algorithm the average delay obtained for server1 was 0.149 seconds and 0.19122. Server2 has an average delay of 0.161 seconds and 0.012 seconds.